Network coded multi-hop video streaming - Mohammed Ayub Bin Dawood (2016)
Currently, high quality video streaming over multi-hop wireless networks proves to be a challenging endeavor due to erratic and time-varying nature of wireless channels and the stringent delivery requirement of video traffic.